Suicide Phenomenon Among Students During the COVID-19 Pandemic: (A Case Study on the Suicide Phenomenon Among Students in Tarakan, North Kalimantan) - Siburian, Donny Paskah Martianus (Universitas Terbuka, 2023)
Abstract This article discusses the impact of the COVID-19 pandemic on human life, particularly in the field of education. In an effort to address the pandemic, the government has implemented Distance Learning Education (PJJ) as a relevant solution, but it has resulted in unintended consequences, including increased stress and suicide among students. This research uses a qualitative method with a case study and sociological analysis using Emile Durkheim's theory of suicide. The analysis results show that suicidal behavior among students occurs due to social symptoms, especially in facing rapid changes and social isolation caused by the COVID-19 pandemic. Students face greater pressure to adapt to these changes, both in their education and social environment. Therefore, appropriate and comprehensive prevention and intervention efforts need to be taken to address this problem and prevent suicide among students. Keywords: Suicide; Online Learning; Stress; Emile Durkheim